ASSESSING THE DEGREE OF MICROBE’S SPREADING ON CHICKEN SOLD IN SOME TRADITIONAL MARKET IN DENPASAR - I M. E., Setyawan; Lindawati, S. A.; Miwada, I N. S. (Jurnal Peternakan Tropika; Vol 5 No 2 (2017), 2017)
The aimed of this study to analyze the level of microbe’s spreading (TPC, Coliform, E.coli ) and the water degree in chiken which sold in some traditional market in Denpasar.  This study took place in Livestock Product Technology and Microbiology laboratory Faculty of Animal Husbandry – Udayana University for 3 months from September until November 2016.  The design which was used for this study was a Randomized Block Design (RBD) with 4 treatments and 4 repititions.  The 4 treatments were Sanglah market (S), Kreneng market (K), Badung market (B) and Pemedilan market (P).  The part of the chicken which was used for this study was the chicken’s chest. This study used 2 step. The first step was descriptive aspects when the cutting process from the beginning until the end was observed fully.  The second step was quantitative analysis including TPC (Total Plate Count), Coliform, E. coli and water degree.  The results showed that TPC in Sanglah markets was 2.77 x 10 8 cfu/g, TPC in Kreneng market was 4.52 x 10 7 cfu/g, TPC in Badung pasar was 7.50 x 10 7 cfu/g and TPC in Pemedilan market was 4.87 x 10 7 cfu/g.  Coliform in Sanglah market was 7.21 x 10 6 cfu/g, Coliform in Kreneng market was 4.42 x 10 6 cfu/g, Coliform in Badung market was 6.17 x 10 6 cfu/g, and Coliform in Pemedilan market was 5.10 x 10 6 cfu/g.  Escherichia coli in Sanglah market was 6.25 x 10 5 cfu/g, Kreneng market 4.12 x 10 5 cfu/g, Badung market 3.55 x 10 6 cfu/g and Pemedilan market 4.72 x 10 4 cfu/g.  The water degree in Sanglah market 75.39% 74.54% Kreneng market, Badung market 75.50% and Pemedilan market 75.86%.  This study concluded that the level of microbe’s spreading in chicken in some some traditional markets in Denpasar was over Indonesia National Standard.